(untitled) (American Journal of Business Management, Economics and Banking, 2024)
This article highlights the significance and benefits of the digital economy in improving internal audit processes within economic entities. It examines the potential of digital technologies to automate internal audit processes, minimize errors, and ensure accurate and timely analysis of financial information. Additionally, the integration of modern tools such as Big Data, cloud technologies, blockchain, and artificial intelligence into internal audit is analyzed, focusing on their ability to enhance transparency, identify risks in advance, and monitor operations effectively. This study demonstrates the role of the digital economy in internal auditing and its positive impact on ensuring the financial stability of organizations.